A copper-based metal–organic framework with a suitable pore environment for effective ethylene purification. Issue 9 (29th March 2022) - Zhang, Xiaolai; Fu, Mingyue; Liu, Hongyan; Wang, Yutong; Zou, Yecheng; Wang, Li; Li, Chenhao; Lu, Yong; Zhou, Liangliang; Cui, Xiangyu
Abstract : Complex 1 based on Cu-MOF with a suitable pore environment and high stability can effectively purify ethylene from any proportion of an ethylene/acetylene mixture. Abstract : Purifying ethylene from an acetylene/ethylene mixture is feasible but challenging because of their similar physical properties. Herein, we synthesized a copper-based metal–organic framework (MOF), namely complex 1, that can preferentially adsorb more C2 H2 than C2 H4 . Breakthrough experiments show that complex 1 can purify the acetylene/ethylene mixture into high-purity ethylene (99.99%) and the productivity is 0.48 mmol g −1 . This work shows that a suitable pore environment will greatly enhance the host–guest interaction, to realize the separation of a similar mixture.